Adolescent Reproductive Health Counseling Activities on the Level of Knowledge of Students of Mts Al-Ihsan, Padang Tikar Village 2024 - Latifah, Nur (Journal of Midwifery and Nursing, 2025)
Background: Adolescence is considered a critical period in the life cycle due to the transition from childhood to adulthood, which is often filled with emotional turbulence. Adolescents experience very rapid changes both physically and emotionally, making them susceptible to the negative impacts of these maturation changes. One of the three main issues in adolescent reproductive health, namely sexuality issues, is greatly influenced by the lack of knowledge adolescents have about their reproductive health. The aim is to determine the effectiveness of reproductive health counseling for adolescents. The method used is a quasi-experiment with a Pre-test and Post-test design, using a questionnaire as the research instrument. The research was conducted in February with a sample of 35 students from MTs AL-IHSAN, Padang Tikar Village, West Kalimantan. The research results show that the knowledge of adolescents after being given counseling on reproductive health is mostly in the good category with a p-value of 0.001. Which means that counseling on adolescents is effective after it has been conducted. Conclusion Based on the results of this study, there is a significant change in the knowledge of adolescents before and after the counseling was conducted.